Risk Perception of Individuals in Human Capital Investment Decision-making from the Perspective of Incomplete Information - Wenxiao Liu (Forest Chemicals Review, 1970)
In the environment of incomplete information, risks and uncertainties have an important impact on human capital investment decisions by individuals. In the research, the investigation of individuals' perception of risks in the process of human capital investment decision-making shows that individuals' attitude towards academic completion risks is cautious but still not optimistic, and the level of employment risks and income acquisition risks is underestimated. The first reason is that individuals do not know the actual situation after entering school because of incomplete information, and the second reason is that the investment income of human capital is wrongly estimated due to confusion of two production processes, difficult change of traditional ideas and the influence of survivors' deviation. In order to improve individual risk perception level, measures such as confirming public demand, enriching information disclosure content, building government-led or regulated information intermediary, establishing long-term effective information transmission mechanism, carrying out individual development guidance, and regulating media information dissemination should be actively taken to minimize the occurrence of decision-making risk.